2012
DOI: 10.1590/s0037-86822012000600009
|View full text |Cite
|
Sign up to set email alerts
|

Triatomines in dwellings and outbuildings in an endemic area of Chagas disease in northeastern Brazil

Abstract: Introduction:The present study identified the triatomines collected in intra and peri-domestic environments, observed the occurrence of Trypanosoma cruzi infection in triatomines and correlated this information with housing conditions and the fauna associated with the rural areas of the City of Itabaianinha, located in the State of Sergipe, Brazil. Methods: Quarterly visits were conducted between March 2009 and March 2010, and the homes to be visited for the active search of insects were determined by random s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
0
13
1
5
Order By: Relevance
“…For municipalities at potential risk for the transmission of CD, the profound environmental changes caused by agricultural production combined with the use of pesticides for controlling insects and other anthropogenic modifications should also be considered. In addition, the consequent reduction of native vegetation coverage and the preferential ecotype of the triatomines forced the vectors to move to the vicinity of human dwellings [ 22 , 40 ]. As a result, the municipality of Cristinápolis, which is located in an area with only 9.64% of its original forest cover and eucalyptus production, was included even though no occurrence of vectors has been reported, but cases of positive serology for human CD were recorded [ 27 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For municipalities at potential risk for the transmission of CD, the profound environmental changes caused by agricultural production combined with the use of pesticides for controlling insects and other anthropogenic modifications should also be considered. In addition, the consequent reduction of native vegetation coverage and the preferential ecotype of the triatomines forced the vectors to move to the vicinity of human dwellings [ 22 , 40 ]. As a result, the municipality of Cristinápolis, which is located in an area with only 9.64% of its original forest cover and eucalyptus production, was included even though no occurrence of vectors has been reported, but cases of positive serology for human CD were recorded [ 27 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another common feature in the interior of this state is the construction of home annexes for housing animals (e.g., cattle, goats, pigs, and chickens). Lima et al [ 22 ] found that the presence of positive triatomines in the rural properties of Sergipe is related to the variety of reared animals and the number of home annexes built to house these animals. Figueiredo et al [ 44 ] observed a strong influence of ecological aggressions on the migration of triatomines toward man-made artificial ecotopes, because these places provide easy access to food, shelter, and protection against natural enemies.…”
Section: Resultsmentioning
confidence: 99%
“…4 O processo de domiciliação triatomínica ocorre quando estes insetos abandonam seu habitat natural devido à destruição ou modificação deste e migra para residências onde há criação de animais domésticos em peridomicílio com estruturas precárias proporcionando fonte alimentar e abrigo, esse processo influencia a ocorrência e transmissão do Trypanosoma cruzi, uma vez que promove o contato permanente entre os vetores, animais e os seres humanos. 5,6 Os processos envolvidos na domiciliação dos vetores da doença de Chagas são divergentes, alguns consideram um simples oportunismo devido à escassez das fontes naturais de alimento e outros acreditam tratar-se de processo gradual de adaptação, sujeito à seleção natural 1 Conclui-se que há colonização em peridomicílio pela espécie T. Pseudomaculata no município de Aurora e que apesar do baixo índice de infecção natural pelo T. cruzi, apresentada pela espécie T. pseudomaculata, a população local encontra-se susceptível, uma vez que a espécie T. pseudomaculata encontra-se próxima a T. brasilienses e esta é considerada fonte primária de infecção.…”
Section: Introductionunclassified
“…Although the prevalence of CD has decreased in the last decades, a recent meta-analysis estimated CD prevalence in Brazil to be near 2.4% or about 4.6 million Brazilians infected by T. cruzi 15 . However, other transmission mechanisms may keep CD as a public health problem such as the ingestion of food contaminated with T cruzi , causing outbreaks of acute CD and transmission by native vectors in different areas of Brazil 1 , 3 , 5 , 12 , 14 , 21 , 22 , 23 , 27 , 28 .…”
Section: Introductionmentioning
confidence: 99%